2009
DOI: 10.1097/htr.0b013e3181a0b291
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Psychosocial Predictors of Caregiver Distress and Perceived Burden Following Traumatic Brain Injury

Abstract: Caregivers' preinjury functioning is more predictive of global distress, whereas the functioning of the person with injury is more predictive of injury-related burden. Caregivers' medical and psychiatric histories are important considerations when targeting interventions; global stress management strategies may be as important as assisting with injury-related issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 49 publications
7
46
0
2
Order By: Relevance
“…The presence of negative coping strategies was strongly associated with several mental illness symptoms. This finding is corroborated by previous studies investigating coping styles in CR of patients with acquired brain injury [8,14,18,25,32]. Noble at al.…”
Section: Associated Factorssupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of negative coping strategies was strongly associated with several mental illness symptoms. This finding is corroborated by previous studies investigating coping styles in CR of patients with acquired brain injury [8,14,18,25,32]. Noble at al.…”
Section: Associated Factorssupporting
confidence: 93%
“…However, both investigated patient cohorts consisted predominantly of low-grade SAH patients whose course of disease and neurologic outcome differed significantly from high-grade SAH. Another study investigating caregiver distress in patients with moderate to severe TBI showed an association of stress symptoms with the caregiver's medical and psychiatric history and also with the use of escape-avoidance coping style [14]. Given these previous observations, the occurrence of significant mental illness symptoms in CR of patients with severe TBI and high-grade SAH is probable and relevant for the CR's quality of life (QoL).…”
Section: Introductionmentioning
confidence: 97%
“…Unsurprisingly, given the circumstances of caring, psychological distress has also been documented [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Elle n'a également pas d'impact sur l'évaluation de la situation d'aide par l'aidant (Hanks, Rapport, & Vanger, 2007 (Folkman & Lazarus, 1980;Lazarus & Folkman, 1984 (Knight et al, 1998;Sander et al, 2003). Une stratégie d'ajustement centrée sur les émotions est liée à l'augmentation de la détresse, de la dépression et de l'anxiété chez l'aidant (Finset & Anderson, 2000;Davis et al, 2009), en plus de nuire à l'adaptation de l'individu (Lazarus et Folkman, 1984). D'autre part, une stratégie d'ajustement centrée sur le problème est l'indicateur d'un ajustement efficace de la famille (Harris et al, 2001;Turner et al, 2007).…”
Section: Autres Variables Pouvant Influencer La Détresse Psychologiquunclassified